The Impact of Color Psychology in Graphic Design: A Comprehensive Review (International Journal of Scientific Research and Management (IJSRM), 2025)
This study examines the impact of color psychology on graphic design and consumer engagement. Findings indicate that color attributes such as hue, saturation, and brightness significantly influence emotional and cognitive perception. Additionally, the strategic use of colors enhances brand messaging and design effectiveness. Using a quantitative experiment and qualitative analysis, the research reveals that warm colors (65%) generate higher engagement than cool colors (35%). The study provides a practical framework for designers and marketers to optimize visual communication strategies.